2016
DOI: 10.1515/msp-2016-0119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaOH concentration on optical properties of zinc oxide nanoparticles

Abstract: In the present work, powder zinc oxide samples were prepared by varying NaOH concentration (0.1 M -0.4 M) using wet-chemical co-precipitation method. As-synthesized ZnO was characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), photoluminescence (PL) and Raman spectroscopy. Formation of hexagonal wurtzite structure of the ZnO samples has been revealed from XRD studies. This study further suggests reduction in crystallite size from 40 nm to 23 nm with an increase in Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 34 publications
3
48
0
4
Order By: Relevance
“…But at higher supersaturation, crystal nucleation dominates crystal growth, resulting in smaller crystallite size. These obtained results are in fair agreement with the observation ( Figure 9) that by decreasing concentration increases the level of supersaturation, thus crystallite size is reduced [14]. Figure 10 shows that UV-Vis absorption spectrum of ZnO nanopowders using 2.5 M, 5 M and 7.5 M concentration of NaOH synthesized from analytical grade ZnCl 2 and using 2.5 M concentration of NaOH synthesized from battery waste.…”
Section: Particle Size Distributionsupporting
confidence: 88%
See 1 more Smart Citation
“…But at higher supersaturation, crystal nucleation dominates crystal growth, resulting in smaller crystallite size. These obtained results are in fair agreement with the observation ( Figure 9) that by decreasing concentration increases the level of supersaturation, thus crystallite size is reduced [14]. Figure 10 shows that UV-Vis absorption spectrum of ZnO nanopowders using 2.5 M, 5 M and 7.5 M concentration of NaOH synthesized from analytical grade ZnCl 2 and using 2.5 M concentration of NaOH synthesized from battery waste.…”
Section: Particle Size Distributionsupporting
confidence: 88%
“…Profound studies have been done on various factors, such as precursor concentrations, temperature, duration, dopant concentration and solvent medium, pH of the reaction mixture which individually and collectively affects the shape, size and optical properties of ZnO nanoparticles. Various researchers revealed that NaOH concentration plays a vital role in determining the morphology, size, shape and optical band gap of obtained nanostructures [14].…”
Section: Introductionmentioning
confidence: 99%
“…The used preparation procedure was described by Koutu et al [18] but applied with some modifications. Zinc acetate dehydrate (Zn(CH 3 CO 2 ) 2 .2H 2 O) and sodium hydroxide were purchased from CDH.…”
Section: Preparation Of Zinc Oxide Nanoparticles (Zno Nps)mentioning
confidence: 99%
“…The remaining peaks were well matched by films coated on glass substrate and introduced in the aforementioned section for films deposited on FTO substrates, and the high-and low-intensity peaks are given as 931, 1100, 129, 343, 266, 797 cm −1 and 776, 1182, 558, 586, 202, 707, 482 cm −1 . The severe peaks at 931, 343, 266 cm −1 contributed to multiphoton scattering in ZnO [39], ZnWO 4 formation [40], irregularities of Raman scattering in the B 1L mode of ZnO [41], respectively. The peaks exist at 292, 1182, 1316 cm −1 specified as unknown, thereby suggesting to belong to other phases of ZnO structures.…”
Section: Resultsmentioning
confidence: 98%